Keanekaragaman kumbang curculionid pada berbagai tipe penggunaan lahan di kawasan Hutan Harapan, Jambi - Lailatun Najmi; Damayanti Buchori; Hermanu Triwidodo; Woro Anggraitoningsih Noerdjito; Akhmad Rizali (Perhimpunan Entomologi Indonesia, 2018)
Family Curculionidae is a group of beetles (Order Coleoptera) that have an important role in different ecosystems, either as herbivores or pollinators. Land-use change, mainly from natural forest to agriculture area can have negative affect on population of curculionid beetles. The objective of this research was to study seasonal diversity, both in terms of species richness and abundance of curculionid beetles in different land-use types in Hutan Harapan landscape, Jambi. Curculionids were sampled using fogging methods. The study was conducted in four different land-use types i.e. forest, jungle rubber, rubber, and oil palm plantations in both dry (from May to September 2013) and rainy season (from November 2013 to February 2014). Four plot each of 50 m x 50 m were set up in the four land use types. We found 1762 individuals belonging to 12 subfamili and 118 species curculionid beetle. The most abundant species was found in forest (81 species) and the lowest was in the rubber plantations (20 species). The most common curculionid that were found in each land-use type were Curculioninae sp.21 (forest), Entiminae sp.06 (jungle rubber), Scolytinae sp.09 (rubber plantation) and Elaeidobius kamerunicus Faust (oil palm plantations). The highest abundance of curculionid was in oil palm plantations (853 individual) and the lowest was in rubber plantations (33 individual). Land-use type and vegetation diversity affect species richness but not abundant of curculionids. Analysis showed that different season significantly affect composition of curculionid in the forest but it has no effect in other land use types.